Development of Approaches to an Organizational and Functional Structure Creating of the Eurasian Economic Union Digital Transport Corridors Ecosystem - O. V. Miasnikova; T. G. Tabolich (Цифровая трансформация)
The work is devoted to the problem of EAEU’s digital transport corridors ecosystem creating. The purpose of this article is to develop approaches to the organizational and functional structure forming of the digital transport corridors ecosystem and to identify the priorities for creating and saturating with services a National electronic transport and logistics system. The factors and conditions for the development of the international digital transport corridors and the basic developing principles of the organizational and functional scheme of their ecosystem are determined. The organizational and functional structure of the digital transport corridors ecosystem is proposed, the ecosystem's levels are described, the upper-level objectives of the ecosystem organization are determined. The author’s approach to the organization of national platform solutions in the field of transport is substantiated. Unlike the existing ones, it envisages the creation of a “Cluster” of digital platforms, both at the national and supranational levels of the ecosystem, ensuring a “seamless” integration of instrumental, infrastructure and applied digital platforms. Methodological issues of the digital platforms functionality designing for cooperation and coordination of the transportation process participants as well as state regulation have been solved. In the work, general scientific methods were used to cognize economic phenomena and processes (analysis and synthesis, a systematic approach, the dialectical method, methods of composition and decomposition of data, etc.). The main study results were systemic approaches to the organizational and functional structure formation of the digital transport corridors ecosystem, the methodology of the digital platform functionality designing and the methodology of developing services of the electronic logistics digital platform based on a map of the speed of development, significance and level of investment. The solutions to the problems of unification and interoperability of digital platforms are outlined. The using area of the proposed solutions: further creation of the National Electronic Transport and Logistics System in the Republic of Belarus, taking into account the development of the EAEU's digital transport corridors ecosystem.